KOMPONEN MAKNA KATA KERAJINAN TANGAN ANYAMAN DALAM BAHASA DAYAK BAKATI’ PALAYO - Yesi, Lidia; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research describes the words of woven crafts in Dayak Bakati'Palayo language. A common problem in this research is the meaning component of the word woven handicrafts in the Dayak Bakati'Palayo language. The general problem is divided into three subproblems, namely the components of meaning, meaning of words, and semantic functions. This study aims to describe the components of meaning, meaning of words, and semantic functions found in the word woven crafts. This research was conducted using descriptive methods with qualitative forms. Data collection methods use proficiency methods, binary opposition, and structural. This study managed to collect 27 data components of meaning. From 27 data meaning components there are 27 data meaning words. This study also produced 10 semantic roles as sufferers, seven semantic roles as inst rumental, four semantic roles as benefactors, two semantic roles as locatives, two semantic roles as experience, one semantic role as acting, and 1 as an incentive. Keywords : Component of meaning, woven handicrafts, Dayak Bakati'Palayo